Transporte eletrônico em semicondutores porosos baseado na equação de Schrodinger dependente do tempo - Silva, Francisco Wellery Nunes (2012)
We propose in this work a theoretical study, of the properties of a electronic pulse, injected under a external bias, on a porous silicon layer, so that we could define fundamentally the shape of T X V and R X V curves, where T is the transmission coefficient and R is the reflection coefficient of the wave packet, trough the porous region. With this, we could make a simple calculation and obtain information about the electrical current in this material, using the very simple model I=Q/t, where we defined the time of transmission, as the time interval necessary for the electronic pulse to be consumed completely. This kind of approach is already known in the literature, propose by Lebedev and co-workers (1998). Using the definition of charge carrier mobility, we obtained information about it, since the principal aim of this work is the electronic transport in this kind of material, that despite a strong research on porous silicon, since the beginning of the nineties, the transport properties still remains a relatively unexplored area. The major incentive for this study is due to the strong possibility of application of this material in new optoelectronic devices such as LEDs. Along the development of this dissertation, we applied well known techniques for the computational modelling such as effective mass theory, for example, associated with methods like the periodic boundary conditions, and the absorbing boundary conditions. Treating of a quantum system, we begin all the work solving the time dependent Schröedinger equation. To do this task, we have used the numerical method known as Split-Operator, in order to obtain the solutions for this equation. Initially, the calculations in this dissertation where based in an isotropic effective mass, in order to optimise the calculation parameters. After this, we made calculations using an anisotropic effective mass for the different valleys of silicon. All these things leads us to believe that this work have a great importance regarding the contribution to the understanding of transport in electronic systems based on porous silicon, to maintain for some time the applications of this kind of material that was so revolutionary in the twentieth.